3(x-3)-2x=4x+3-5x

Simple and best practice solution for 3(x-3)-2x=4x+3-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-3)-2x=4x+3-5x equation:


Simplifying
3(x + -3) + -2x = 4x + 3 + -5x

Reorder the terms:
3(-3 + x) + -2x = 4x + 3 + -5x
(-3 * 3 + x * 3) + -2x = 4x + 3 + -5x
(-9 + 3x) + -2x = 4x + 3 + -5x

Combine like terms: 3x + -2x = 1x
-9 + 1x = 4x + 3 + -5x

Reorder the terms:
-9 + 1x = 3 + 4x + -5x

Combine like terms: 4x + -5x = -1x
-9 + 1x = 3 + -1x

Solving
-9 + 1x = 3 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-9 + 1x + x = 3 + -1x + x

Combine like terms: 1x + x = 2x
-9 + 2x = 3 + -1x + x

Combine like terms: -1x + x = 0
-9 + 2x = 3 + 0
-9 + 2x = 3

Add '9' to each side of the equation.
-9 + 9 + 2x = 3 + 9

Combine like terms: -9 + 9 = 0
0 + 2x = 3 + 9
2x = 3 + 9

Combine like terms: 3 + 9 = 12
2x = 12

Divide each side by '2'.
x = 6

Simplifying
x = 6

See similar equations:

| 5-(2-27)= | | 4d(2d-8)= | | -2x^2-4x+7=0 | | Log(5x+3)=2 | | (y+1)*(y+2)=30 | | 13x^2-45x=0 | | (19x-18)+(-5x+2)= | | 0.45-9=0.9 | | 4x^2=-3x-8 | | 3+4x-1=x+14+x-4 | | 8m-6=-5m+15 | | -3x/4-2 | | .25x+.10(9-x)=2.5 | | x^2+x+2y^2-16y+32=0 | | 3q+7=q-13 | | 3=6-2(x-3) | | y=-x^2+16 | | 15y-8=10y+2 | | 5x+7=3(x+4) | | .74=11612000-x/5246000 | | 1+192837465x-d=231111111116666666 | | 4/b-7/d= | | 55x-9+g=100007 | | 4/(x-6)=5 | | 55x-9+g= | | 3t+19-5t=91 | | z^2(4z^3-10)=0 | | u/4=0 | | 5p^2+30x=0 | | 4x-1=2(x-5) | | 5c+17-8c=156 | | 2=p/6 |

Equations solver categories